Lecturers' reflections on the teaching of social sciences in a multidisciplinary context at a university in South Africa. Issue 2 (3rd March 2020) - Kgari-Masondo, Christina; Ngwenya, Jabulisile
ABSTRACT: The article offers detailed reflections of two lecturers on the teaching of Social Sciences Education Honours modules in a multidisciplinary context at one university in South Africa. The reflections portray that, while in Social Sciences Education students from diverse specialisations are enrolled in courses that are multidisciplinary in nature, the teaching pedagogy used continues to be disciplinary-based. Through the qualitative self-reflective narrative study of two lecturers teaching Commerce Education and History Education in the Honours programme in this university, the paper explores how these lecturers teach these Honours modules in a multidisciplinary context. Drawing on the reflections of the two lecturers, the conclusions of the study were that, the Honours programme in Social Sciences Education needs to be an integrated and multidisciplinary study, given the pedagogical weaknesses, and the resultant compromising of the quality of the teaching of the disciplines within this programme. The paper proposes 'border crossing pedagogy' as a solution that can be used in a multidisciplinary classroom because it allows for integration of disciplines in terms of content and teaching approach. This calls for revisiting how the modules within Social Sciences Honours programme are taught in South Africa.